Characterization and Association of CFHR5 Gene Polymorphism with Fatty Acid Composition and Cholesterol in Sheep - Akbanugra Yudhananda; Kasita Listyarini; Cece Sumantri; Asep Gunawan (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
The Complement Factor H Related 5 (CFHR5) gene is speculated to have an important role in regulating fatty acid composition in sheep. The aim of this study was to investigate the polymorphism of the CFHR5 gene and its association with fatty acid composition and cholesterol of sheep in Indonesia. A total of 172 rams from 83 priangan sheep (PS), 20 sapudi sheep (SS), 19 Garut sheep (GS), 20 jonggol sheep (JS), 10 Garut composite sheep (GCS), 10 compass agrinac sheep (CAS), and 10 Barbados cross sheep (BCS) were used for this study. Identification of CFHR5 gene polymorphism were performed by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) using AciI restriction enzyme. The results showed that the CFHR5 gene in all sheep populations were polymorphic producing three genotypes, e.g. CC, CT and TT, respectively. The polymorphism had a significant effect (p<0.05) on fatty acid composition (miristoleic [C14:1], ginkgolic [C17:1], tridecanoic [C13:0], and heptadecanoic [C17:0] acids) and cholesterol. The breed and polymorphism had a significant effect (p<0.05) on fatty acid composition (JS with tridecanoic acid [C13:0] and BCS with miristoleic acid [C14:1]). The CC genotype is the preferred genotype and as it exhibits reduced levels of saturated fatty acids and cholesterol. The BCS sheep is the preferred genotype and as it exhibits high PUFA/SFA ratio. The CFHR5 gene (SNP c.1011C>T) has the potential to be used as a genetic marker for the selection of low saturated fatty acid composition and cholesterol in sheep